2015
DOI: 10.1186/s12870-015-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing expressed sequence tag libraries and the discovery of simple sequence repeat markers for two species of raspberry (Rubus L.)

Abstract: BackgroundDue to a relatively high level of codominant inheritance and transferability within and among taxonomic groups, simple sequence repeat (SSR) markers are important elements in comparative mapping and delineation of genomic regions associated with traits of economic importance. Expressed sequence tags (ESTs) are a source of SSRs that can be used to develop markers to facilitate plant breeding and for more basic research across genera and higher plant orders.MethodsLeaf and meristem tissue from ‘Heritag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Moreover, a specific feature in the Rubus spp. breeding system is that multiple species are often utilized in breeding programs [7]. Scientific achievements in molecular biology, and use of molecular markers, in particular, can accelerate the selection process, as they will allow for the assessment of the seedlings with valuable traits at a much earlier stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a specific feature in the Rubus spp. breeding system is that multiple species are often utilized in breeding programs [7]. Scientific achievements in molecular biology, and use of molecular markers, in particular, can accelerate the selection process, as they will allow for the assessment of the seedlings with valuable traits at a much earlier stage.…”
Section: Introductionmentioning
confidence: 99%
“…They are very polymorphic with high information content, co-dominant inheritance, locus specificity, extensive genome coverage and simple detection using labelled primers that flank the microsatellite [9,21], and their ability to distinguish even closely related individuals is particularly important for many crop species [21]. Raspberry researchers have noted the benefits of the SSR markers, but very few molecular markers still exist for Rubus [7,22]. It should be also acknowledged that the breeding process can be accelerated using genomic selection (e.g., [23]), an approach under rapid adoption in many species, which is based on multiple marker-trait associations and does not require linkage maps.…”
Section: Introductionmentioning
confidence: 99%
“…A good choice for breeding purposes is a simple sequence repeat (SSR) or microsatellite markers consisting of tandem repeats (1-6 nucleotides). Due to their codominant inheritance, high level of polymorphism, and abundance in genome, they play an important role in identifying genomic regions associated with the traits of economic importance [13]. SSR markers for the Rubus and Fragaria species were first developed in the early 2000s [14,15] and in subsequent years, a number of studies were carried out, including evaluation of marker transferability.…”
Section: Introductionmentioning
confidence: 99%
“…In raspberry breeding, interspecific hybridization is widely used, and development of molecular genetic markers that can be transferred between different species, especially with different ploidy, becomes an important task. However, very few molecular genetic markers are known for Rubus, and fewer are transferable between species [13]. All strawberry cultivars now available at the market have been produced using traditional breeding methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…EST-SSRs from Rubus L. are scarce. Overall, 1149 ESTs were obtained from the cDNA library of the red raspberry cultivar Heritage, and 131 SSR-containing sequences were acquired (Bushakra et al, 2015). In this study, in total, 11,158 SSR-containing unigenes and 235 SSR motifs were identified from 59,173 unigenes after transcriptome assembly and SSR search, and 18.67% unigenes included the SSR sequences.…”
Section: Discussionmentioning
confidence: 99%